PD-L1 immunohistochemistry for canine cancers and clinical benefit of anti-PD-L1 antibody in dogs with pulmonary metastatic oral malignant melanoma - Naoya Maekawa (Nature Portfolio, 2021)
Abstract Immunotherapy targeting programmed cell death 1 (PD-1) and PD-ligand 1 (PD-L1) represents promising treatments for human cancers. Our previous studies demonstrated PD-L1 overexpression in some canine cancers, and suggested the therapeutic potential of a canine chimeric anti-PD-L1 monoclonal antibody (c4G12). However, such evidence is scarce, limiting the clinical application in dogs. In the present report, canine PD-L1 expression was assessed in various cancer types, using a new anti-PD-L1 mAb, 6C11-3A11, and the safety and efficacy of c4G12 were explored in 29 dogs with pulmonary metastatic oral malignant melanoma (OMM). PD-L1 expression was detected in most canine malignant cancers including OMM, and survival was significantly longer in the c4G12 treatment group (median 143 days) when compared to a historical control group (n = 15, median 54 days). In dogs with measurable disease (n = 13), one dog (7.7%) experienced a complete response. Treatment-related adverse events of any grade were observed in 15 dogs (51.7%). Here we show that PD-L1 is a promising target for cancer immunotherapy in dogs, and dogs could be a useful large animal model for human cancer research.